Risk factors for loss to follow-up in patients with gout: A Korean prospective cohort study - Hyunsue Do; Chang-Nam Son; Hyo Jin Choi; Ji Hyoun Kim; Min Jung Kim; Kichul Shin; Sang-Hyon Kim; Byoongyong Choi; You-Jung Ha; Joong Kyong Ahn; Hyun-Ok Kim; Sung Won Lee; et al. (PLoS ONE, 2025)
Objectives Gout, a common form of inflammatory arthritis, is often managed with urate-lowering therapy, but many patients only adhere to treatment during gout attacks, resulting in poor follow-up and suboptimal management. This study aimed to identify characteristics associated with loss to follow-up (LTFU) and develop strategies for better patient management. Methods Data were analyzed from the Urate Lowering TheRApy in gout (ULTRA) registry, a prospective cohort of Korean gout patients recruited since September 2021. Patients aged 18 or older who met the 2015 ACR/EULAR classification criteria were included. Demographic data, clinical characteristics, lifestyle habits, comorbidities, and quality of life assessments using the Korean Gout Impact Scale (K-GIS) and EuroQol 5-Dimension (EQ-5D) were collected at baseline, six months, and annually. LTFU was defined as missing a clinic visit for more than a year. Logistic regression was used to determine factors associated with LTFU. Results Among 269 patients, 125 (46.5%) were classified as LTFU. Patients not lost to follow-up experienced more frequent gout attacks (P = 0.020) and expressed greater concerns about future flares (P = 0.034). In contrast, LTFU patients had higher levels of anxiety (P = 0.049), depressive symptoms (P = 0.009), impaired mobility (P = 0.002), and a higher EQ-5D score (P = 0.002). Logistic regression identified frequent gout attacks, concerns about attacks, anxiety, impaired mobility, and EQ-5D scores as significant predictors of LTFU. Conclusion Fewer gout attacks, heightened anxiety and depression, and lower quality of life were key factors associated with LTFU. Providing emotional support and comprehensive education may enhance follow-up and improve gout management.